Effects of urban motorways on physical activity and sedentary behaviour in local residents: a natural experimental study - R. G. Prins; L. Foley; N. Mutrie; D. B. Ogilvie; on behalf of the M74 study team (BMC, 2017)
Abstract Background There is little evidence on how changing the physical environment changes health-related behaviours. We studied the effects of the new M74 motorway (freeway) - opened in 2011 - and the existing M8 motorway in Glasgow, Scotland, on physical activity and sedentary behaviour among local residents. Methods This natural experimental study used baseline (T1; 2005) and follow-up data (T2; 2013) from a longitudinal cohort (N = 365) and two cross-sectional samples (T1 N = 980; T2 N = 978). Adult participants were recruited from three study areas: one surrounding the new motorway, one surrounding the existing motorway, and a third, control, area without a motorway. The outcomes were self-reported time spent sitting, walking, and in moderate-to-vigorous physical activity (MVPA). Motorway exposure was defined in terms of (1) study area and (2) distance from home to the nearest motorway junction. Outcomes were regressed on exposures in two-part (walking and MVPA) or linear (sedentary behaviour) cohort and repeat cross-sectional models, adjusted for baseline behaviour and sociodemographic covariates. Results Cohort participants living in the M8 area were less likely to participate in MVPA at follow-up than those living in the area without a motorway (OR 0.37; 95%CI 0.15, 0.91). Within the M8 area, those living closer to the motorway were also less likely to do so (OR 0.30; 95%CI 0.09, 0.97). No other statistically significant results were found. Conclusions We found some evidence of a negative association between exposure to an existing urban motorway and MVPA. However, the behavioural impacts of motorways are likely to be complex and evolve over time.